Understanding the Unique Electronic Properties of Nano Structures Using Photoemission Theory - Kwon, Soonnam; Choi, Won Kook (NATURE PUBLISHING GROUP, 2015)
Newly emerging experimental techniques such as nano-ARPES are expected to provide an opportunity to measure the electronic properties of nano-materials directly. However, the interpretation of the spectra is not simple because it must consider quantum mechanical effects related to the measurement process itself. Here, we demonstrate a novel approach that can overcome this problem by using an adequate simulation to corroborate the experimental results. Ab initio calculation on arbitrarily-shaped or chemically ornamented nano-structures is elaborately correlated to photoemission theory. This correlation can be directly exploited to interpret the experimental results. To test this method, a direct comparison was made between the calculation results and experimental results on highly-oriented pyrolytic graphite (HOPG). As a general extension, the unique electronic structures of nano-sized graphene oxide and features from the experimental result of black phosphorous (BP) are disclosed for the first time as supportive evidence of the usefulness of this method. This work pioneers an approach to intuitive and practical understanding of the electronic properties of nano-materials.
Keywords: ANGLE-RESOLVED PHOTOEMISSION; PHOTOIONIZATION CROSS-SECTIONS; FIELD-EFFECT TRANSISTORS; GRAPHENE; APPROXIMATION; NANORIBBONS; ORIENTATION; SURFACE; COPPER